'Obesities': Position statement on a complex disease entity with multifaceted drivers. (12th May 2022) - Yárnoz‐Esquiroz, Patricia; Olazarán, Laura; Aguas‐Ayesa, Maite; Perdomo, Carolina M.; García‐Goñi, Marta; Silva, Camilo; Fernández‐Formoso, José Antonio; Escalada, Javier; Montecucco, Fabrizio; Portincasa, Piero; Frühbeck, Gema
Abstract: Academic medicine fosters research that moves from discovery to translation, at the same time as promoting education of the next generation of professionals. In the field of obesity, the supposed integration of knowledge, discovery and translation research to clinical care is being particularly hampered. The classification of obesity based on the body mass index does not account for several subtypes of obesity. The lack of a universally shared definition of "obesities" makes it impossible to establish the real burden of the different obesity phenotypes. The individual's genotype, adipotype, enterotype and microbiota interplays with macronutrient intake, appetite, metabolism and thermogenesis. Further investigations based on the concept of differently diagnosed "obesities" are required.